2021
DOI: 10.1186/s43014-021-00073-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, phytochemical and antioxidant properties of 24 mung bean (Vigna radiate L.) genotypes

Abstract: This study aimed to investigate the proximate and phytochemicals present in seeds of 24 mung bean (Vigna radiate L.) genotypes from four provinces of China for estimating their nutritional and antioxidant properties. Proximate analysis of mung bean genotypes revealed that starch, protein, fat, ash and water-soluble polysaccharide ranged from 39.54–60.66, 17.36–24.89, 4.24–12.18, 2.78–3.53 and 1.99–2.96 g/100 g respectively. The five principal fatty acids detected in mung beans were stearic acid, palmitic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…(Sha'a, 2021). As reported Wang et al (2021), five principal fatty acids were found in seed raw such as palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid.…”
Section: Introductionmentioning
confidence: 60%
“…(Sha'a, 2021). As reported Wang et al (2021), five principal fatty acids were found in seed raw such as palmitic acid, stearic acid, oleic acid, linoleic acid, and linolenic acid.…”
Section: Introductionmentioning
confidence: 60%
“…A total of 40 soybean cultivars from various ecotype regions and maturity stages in China had total isoflavone contents ranging from 55.1 to 758.4 mg/100 g as determined by HPLC analysis [ 28 ]. While using the same detection method, total isoflavone content ranging from 0.69 to 5.42 mg/g dry matter were detected in 23 soybeans at 4 different maturity stages from Serbia [ 8 ], while vitexin and isovitexin were dominantly detected in 24 mung bean genotypes collected in different regions of China [ 6 ]. Globally, the average isoflavone content was 154.53 mg/100 g soybean [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These were mostly flavonoids including kaempferol, quercetin and their derivatives [ 5 ]. Four phenolic acids (caffeic acid, p -coumaric acid, ferulic acid and syringic acid) and two flavonoids (vitexin and isovitexin) were dominantly found in mung beans ( Vigna radiate L.) harvested from different regions in China [ 6 ]. Furthermore, isoflavones, which are subtypes of flavonoids that resemble the sex hormone, estrogen (phytoestrogens), have also been identified in beans, such as daidzein, daidzin, glycitein, glycitin, genistein and genistin [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some phenolic compounds present in this legume, which increase with processes such as germination and fermentation according to [ 16 ], could be used in chemoprevention of certain diseases. These compounds are functional food ingredients in mung bean, having a wide range of biological activities including antioxidant [ 17 ], anti-inflammatory, antidiabetic [ 18 ], antiviral, anticancer, antitumor [ 13 ], hepatoprotective [ 19 ], antibacterial, antifungal, and other detoxification activities [ 20 ]. Thus, the mung bean selected, cultivated, and consumed in Burkina Faso could serve as a functional food in the prevention and management of cancer, the prevalence of which is constantly increasing in the country like in other middle-income countries.…”
Section: Introductionmentioning
confidence: 99%